Perceived Ease Of Use, Perceived Usefulness And Satisfaction To Maximize Behavioral Intention With The Technology Acceptance Model In Generation Y And Z Consumers - Denovan, Rheza Farrel; Marsasi, Endy Gunanto (LPPM Universitas Trunojoyo Madura, 2025)
Video conferencing services have become an essential part of modern digital life, especially in the world of remote work. Video conferencing platforms allow people to stay connected and collaborate effectively. This study aims to identify the impact of perceived usefulness and ease of use and verify the impact of satisfaction and attitude in maximizing behavioral intentions. This study adds satisfaction variables as a novelty to this study and uses the Technology Acceptance Model as the main theory. The method in this study uses a quantitative approach with a purposive sampling technique that produces 203 samples. This study uses SEM analysis with the help of Amos Graphic software as a data processing tool. This study found that the perception of trust has a significant positive effect on perceived ease. This study also proves that perceived ease has a significant positive effect on perceived usefulness and attitude. Perceived usefulness has a significant positive effect on satisfaction and a significant negative effect on attitude. Behavioral intentions in this study are significantly positively influenced by attitudes but not by satisfaction. This research can also help companies and managers in the video conferencing services industry. Companies or managers can understand the factors that influence perceived usefulness, perceived ease of use, and satisfaction in developing marketing strategies. Discussion of several variables that influence consumer behavioral intentions on video conferencing services. Behavioral intentions are not only influenced by satisfaction and attitude toward use, but there are still other factors that can encourage consumers' behavioral intentions to continue using services on an ongoing basis.